2013
DOI: 10.1111/evo.12112
|View full text |Cite
|
Sign up to set email alerts
|

EVOLUTIONARY RESPONSES OF A COCCOLITHOPHORIDGEPHYROCAPSA OCEANICATO OCEAN ACIDIFICATION

Abstract: The ongoing ocean acidification associated with a changing carbonate system may impose profound effects on marine planktonic calcifiers. Here, we show that a coccolithophore, Gephyrocapsa oceanica, evolved in response to an elevated CO 2 concentration of 1000 µatm (pH reduced to 7.8) in a long-term (∼670 generations) selection experiment. The high CO 2 -selected cells showed increases in photosynthetic carbon fixation, growth rate, cellular particulate organic carbon (POC) or nitrogen (PON) production, and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 46 publications
(50 reference statements)
4
78
0
Order By: Relevance
“…For photosynthesis however, light requirements for maximum rates are halved at 1,500 µatm in comparison to 500 µatm. It may be that increased f CO 2 , through increased substrate availability, reduces the need for CO 2 concentrating mechanisms (CCMs) (Jin et al, 2013). As CCMs require energy to function, a reduction in their activity would result in a lower energy demand (Barcelos e Ramos et al, 2010), and therefore a lower light requirement for photosynthesis, and to a lesser degree calcification (Jin et al, 2013).…”
Section: Light Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…For photosynthesis however, light requirements for maximum rates are halved at 1,500 µatm in comparison to 500 µatm. It may be that increased f CO 2 , through increased substrate availability, reduces the need for CO 2 concentrating mechanisms (CCMs) (Jin et al, 2013). As CCMs require energy to function, a reduction in their activity would result in a lower energy demand (Barcelos e Ramos et al, 2010), and therefore a lower light requirement for photosynthesis, and to a lesser degree calcification (Jin et al, 2013).…”
Section: Light Responsesmentioning
confidence: 99%
“…It may be that increased f CO 2 , through increased substrate availability, reduces the need for CO 2 concentrating mechanisms (CCMs) (Jin et al, 2013). As CCMs require energy to function, a reduction in their activity would result in a lower energy demand (Barcelos e Ramos et al, 2010), and therefore a lower light requirement for photosynthesis, and to a lesser degree calcification (Jin et al, 2013). The dependence of light responses on f CO 2 could have important implications for coccolithophores under future ocean conditions where both f CO 2 and light availability is expected to change.…”
Section: Light Responsesmentioning
confidence: 99%
“…at high CO 2 demonstrated that some adapted cell lines lost CCM capabilities (Collins and Bell 2004;Collins et al 2006). Lohbeck et al (2012) found that 500 generations of selection at high CO 2 led to recovery of a coccolithophore's growth rates and calcification, although 680 generations of selection at high CO 2 did not show such a trend in Gephyrocapsa oceanica (Jin et al 2013b). (6) Monitoring community abundance of diatoms together with other key taxa over longer time scales is important to gain in situ information on their responses to environmental changes (Mutshinda et al 2013 …”
Section: Future Effortsmentioning
confidence: 99%
“…Hence, the bioassays tested coccolithophore sensitivity to sharp changes in carbonate chemistry rather than acclimation to ocean acidification processes occurring over decades per se. In this context, even results generated through long-term experiments (Lohbeck et al, 2012;Jin et al, 2013) must be interpreted with caution, as the timescale is still an order of magnitude lower than the hundreds of generations or adaptation periods of microbes to ocean acidification in nature (Richier et al, 2014a).…”
Section: Coccolithophore Calcification In Relation To Carbonate Chemimentioning
confidence: 99%